BN-PR manifesto war : different platforms, same school - Shamsul A. B (2013)
The ruling Barisan Nasional coalition and the opposition Pakatan Rakyat have been engaged in a war of manifestos. While each side claims to offer better programmes and plans than the other, their leaders, Najib Razak and Anwar Ibrahim, come from the same school - the 'BN Political Academy'- and are essentially cut from the same cloth.